2014
DOI: 10.1007/s13197-013-1237-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of supercritical fluid extraction of anthocyanin and phenolic compounds from Syzygium cumini fruit pulp

Abstract: Supercritical carbon dioxide extraction (SC-CO 2 ) of total anthocyanin and phenolic compounds from jamun fruits was investigated using three factors at three levels Box-Behnken response surface design. Experiments were conducted to evaluate the effects of three independent variables (pressure, temperature and co-solvent flow rate) on the maximum extraction yield of anthocyanin and phenolic compounds from jamun fruits. From the experimental data, second order polynomial mathematical models were developed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 31 publications
2
52
0
1
Order By: Relevance
“…PRESS value was very lower (0.26) in this study and indicated the perfectness of the developed model. In this study, the adequate precision (signal to noise ratio) was found to be > 70 for the responses, which indicated the best fitness of the developed models [14].…”
Section: Experimental Data Analysismentioning
confidence: 61%
“…PRESS value was very lower (0.26) in this study and indicated the perfectness of the developed model. In this study, the adequate precision (signal to noise ratio) was found to be > 70 for the responses, which indicated the best fitness of the developed models [14].…”
Section: Experimental Data Analysismentioning
confidence: 61%
“…Gallic acid, caffeic acid, sinapic acid, quercetin and delphinidin eluted at retention time of 16.9, 43.6, 63.4, 86.3 and 45.1 min, respectively, showed concentration of 41.4, 65.6, 21.3, 14.9 and 20.2 mg/ml, respectively. Maran, Priya, and Manikandan (2014) previously identified these compounds in jambolan fruit pulp. Similarly, Faria, Marques, and Mercadante (2011) also identified the major anthocyanin and nonanthocyanin compounds as delphinidin-3-glucoside, myricetin and gallic acid in jambolan.…”
Section: Resultsmentioning
confidence: 99%
“…In order to test the hypotheses on the factors of the model, all variations are subdivided into component parts combined with specific sources of variations by ANOVA [32]. The statistical analysis results are displayed in Table 3.…”
Section: Rsm Modeling and Optimization Of Microwave-assisted Esterifimentioning
confidence: 99%